CdSe/ZnS quantum dot encapsulated MoS2 phototransistor for enhanced radiation hardness - Park, Jinwu; Yoo, Geonwook; Heo, Junseok (Scientific Reports, 2019)
Notable progress achieved in studying MoS2 based phototransistors reveals the great potential to be applicable in various field of photodetectors, and to further expand it, a durability study of MoS2 phototransistors in harsh environments is highly required. Here, we investigate effects of gamma rays on the characteristics of MoS2 phototransistors and improve its radiation hardness by incorporating CdSe/ZnS quantum dots as an encapsulation layer. A 73.83% decrease in the photoresponsivity was observed after gamma ray irradiation of 400 Gy, and using a CYTOP and CdSe/ZnS quantum dot layer, the photoresponsivity was successfully retained at 75.16% on average after the gamma ray irradiation. Our results indicate that the CdSe/ZnS quantum dots having a high atomic number can be an effective encapsulation method to improve radiation hardness and thus to maintain the performance of the MoS2 phototransistor.